PENGARUH RASIO KEUANGAN TERHADAP TINGKAT BAGI HASIL SIMPANAN MUDHARABAH BANK SYARIAH (SURVEI PADA BANK SYARIAH MANDIRI DAN BANK MUAMALAT INDONESIA PERIODE 2006-2008) - Popy Turlina Sri Handayani; Ahim Abdurahim (Universitas Muhammadiyah Yogyakarta, Indonesia, 2009)
The existence of Islamic (syari'ah) banks in Indonesia is officially recognized after the lauch of the Banking Enactment No. 7, 1992 (UU No. 7 Tahun 1992 tentang Perbankan) during the economic crisis, Islamic bank, especially Bank Muamalat Indonesia and Bank Syariah Mandiri have proved that banks operating under the profit sharing schemes can survive amid the high fluctuation of exchange rates and interest rates. This study aims at examining the financing ratios on the profit-sharing rates of mudharabah savings in Bank Muamalat Indonesia and Bank Syariah Mandiri for the years of 2006-2008. Data are analyzed based on the classical assumption testing and hypothesis testing using multiple linear regression analysis. The results suggest the presence of multicolleniearity in the classical assumption testing. Howevet. simultaneity test suggests that the impact of the ratios such as ROA, ROE, FDR, BOPO, NIM and GAR on the profit-sharing rates (TBH), whereas partial testing shows two variables such as FDR and GAR do not influence the profit-sharing rates for mudharabah savings.